Long COVID: post-acute sequelae of COVID-19 with a cardiovascular focus - Raman, B; Bluemke, D; Lüscher, T; Neubauer, S (Oxford University Press, 2022)
Emerging as a new epidemic, long COVID or Post-Acute Sequelae of COVID-19 (PASC), a condition characterised by the persistence of COVID-19 symptoms beyond 4 weeks, is anticipated to substantially alter the lives of millions of people globally. Cardiopulmonary symptoms including chest pain, shortness of breath, fatigue and autonomic manifestations such as postural orthostatic tachycardia are common and associated with significant disability, heightened anxiety and public awareness. A range of cardiovascular abnormalities has been reported among patients beyond the acute phase and include myocardial inflammation, myocardial infarction, right ventricular dysfunction and arrhythmias. Pathophysiological mechanisms for delayed complications are still poorly understood, with a dissociation seen between ongoing symptoms and objective measures of cardiopulmonary health. COVID-19 is anticipated to alter the long term trajectory of many chronic cardiac diseases which are abundant in those at risk of severe disease. In this review, we discuss the definition of long COVID and its epidemiology, with an emphasis on cardiopulmonary symptoms. We further review the pathophysiological mechanisms underlying acute and chronic cardiovascular injury, the range of post-acute cardiovascular sequelae and impact of COVID-19 on multiorgan health. We propose a possible model for referral of post-COVID-19 patients to cardiac services and discuss future directions including research priorities and clinical trials that are currently underway to evaluate the efficacy of treatment strategies for long COVID and associated cardiovascular sequelae.